Evaluation of Layout Design, Operation and Maintenance of Multi Automated Systems Guided Vehicles (AGV): A Review - Suparjon, Suparjon (International Journal of Mechanical Engineering Technologies and Applications, 2022)
Automated Guided Vehicle (AGV) is a type of vehicle that is driverless and is programmed to run on a predetermined route to transfer loads. Thus, the aim of this work is to improve the layout, operation, and maintenance. the results of these objectives explain that many are used in AGV systems for modern material handling due to the ability of this technology to increase the efficiency and productivity of the system and reduce human labor. Flow paths or layouts are fixed guided routes where vehicles can travel to various points of collection and delivery of cargo. Avoiding collision and deadlock situations, traffic management is required. To prevent physical collisions and obstacles in the path, sensors must be installed AGV. Automatic vehicle maintenance, we must remain vigilant when the AGV is operating, therefore we are very wary of accidents, as explained above that autonomous car will be programmed to follow the flow path rules and reduce the number of accidents but apply to the safety of the driver and look for situations which is less dangerous. After analyzing the situation and doing so choose the best option. Thus, the maintenance of the AGV must be intensive so that automotive vehicle accidents cannot occur again.